Analisis Struktural Naskah Drama Bila “Malam Bertambah Malam” Karya Putu Wijaya - Jelita Maulida Nurhamidah; Rita Rismawati; Adita Widara Putra (Lembaga Pengembangan Kinerja Dosen, 2024)
This study examines the importance of structural analysis in understanding the depth of a literary work, particularly the drama script